Follow-up of the IceCube alerts with the Baikal-GVD telescope. (24th November 2021) - Dik, V.Y.; Allakhverdyan, V.A.; Avrorin, A.D.; Avrorin, A.V.; Aynutdinov, V.M.; Bannasch, R.; Bardačová, Z.; Belolaptikov, I.A.; Borina, I.V.; Brudanin, V.B.; Budnev, N.M.; Dik, V.Y.; et al.
Abstract: The high-energy muon neutrino events of the IceCube telescope, that are triggered as neutrino alerts in one of two probability ranks of astrophysical origin, "gold" and "bronze", have been followed up by the Baikal-GVD in a fast quasi-online mode since September 2020. Search for correlations between alerts and GVD events reconstructed in two modes, muon-track and cascades (electromagnetic or hadronic showers), for the time windows ±1 h and ±12 h does not indicate statistically significant excess of the measured events over the expected number of background events. Upper limits on the neutrino fluence will be presented for each alert.